Developing the Educational and Rehabilitation Needs Scale for Children With Down Syndrome (Parent Form) in Iran: A Mixed Method Study - Nayereh Naghdi; GholamAli Afrooz; Saeid Hassanzadeh; Sogand Ghasemzadeh (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Despite the existence of various tools to assess such children's educational and rehabilitation needs, there is no instrument in Persian for this purpose. The present study aims to develop a questionnaire to measure the educational and rehabilitation needs of children with Down syndrome in Iran from the perspective of their mothers.Methods This is a mixed method study with exploratory design-instrument development model. The phenomenological method was used in the qualitative stage, where the participants were 17 mothers of children with Down syndrome in Iran who were selected purposefully based on theoretical saturation. In this phase, semi-structured interviews were used. Hsieh and Shannon's content analysis method was used to analyze the data. In the quantitative phase, participants were 100 mothers of children with Down syndrome who were selected using a random sampling method. In this phase, a researcher-made questionnaire of educational and rehabilitation needs of children with Down syndrome was used. Then, its validity and reliability were determined.Results According to mothers, children with Down syndrome have four main needs: Communication skills, adaptive behaviors, language skills, and educational problems. These were considered as the subscales of the questionnaire. The content validity ratio (CVR) was in the range of 0.8-1, and the content validity index (CVI) value was 0.98. The Cronbach's alpha for the overall scale was 0.93. The test-retest coefficient for the overall scale was 0.84.Conclusion The educational and rehabilitation needs scale for children with Down syndrome (parent form) in Persian has acceptable validity and reliability.